2021
DOI: 10.14202/vetworld.2021.3119-3125
|View full text |Cite
|
Sign up to set email alerts
|

Validation of single-step genomic predictions using the linear regression method for milk yield and heat tolerance in a Thai-Holstein population

Abstract: Background and Aim: Genomic selection improves accuracy and decreases the generation interval, increasing the selection response. This study was conducted to assess the benefits of using single-step genomic best linear unbiased prediction (ssGBLUP) for genomic evaluations of milk yield and heat tolerance in Thai-Holstein cows and to test the value of old phenotypic data to maintain the accuracy of predictions. Materials and Methods: The dataset included 104,150 milk yield records collected from 1999 to 2018 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Our results showed only a small improvement in stability between ABLUP and HBLUP in the single population , whereas other studies have demonstrated more marked increases caused by the addition of genomic information (e.g. Cesarani, Biffani, et al 2021 ; Kluska et al 2021 ; Sungkhapreecha et al 2021 ). Including MF improved our HBLUP model stability by 0.01 in the single population and 0.03 in the joint population , while it had mixed impacts on stability across 4 traits in Kluska et al (2021) .…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Our results showed only a small improvement in stability between ABLUP and HBLUP in the single population , whereas other studies have demonstrated more marked increases caused by the addition of genomic information (e.g. Cesarani, Biffani, et al 2021 ; Kluska et al 2021 ; Sungkhapreecha et al 2021 ). Including MF improved our HBLUP model stability by 0.01 in the single population and 0.03 in the joint population , while it had mixed impacts on stability across 4 traits in Kluska et al (2021) .…”
Section: Discussioncontrasting
confidence: 95%
“…In Bradford et al ’s (2019) simulation study, an incomplete population displayed large positive bias by ABLUP, a much smaller negative bias by HBLUP, and effectively no bias by HBLUP with MF. Cesarani, Biffani, et al (2021) and Sungkhapreecha et al (2021) both found that biases present in ABLUP models were greatly diminished using HBLUP on the same populations. In contrast, Granado-Tajada et al (2020) found that bias in dairy sheep evaluations was greater for HBLUP than ABLUP, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Misztal et al [20] reported that the accuracy of the GEBVs was greater than that of the pedigree-based EBVs. At the same time, Sungkhareecha et al [43] reported that the rate of genetic progress from the top 20% of the herd found that the ssGBLUP method was faster than the traditional BLUP method in milk traits, and it would be helpful for increasing the selection accuracy and reducing the costs of progeny testing. Although the accuracy of the GEBVs was already sufficiently high for dairy cattle, the adoption of the technology has been widespread, and future work will focus on improving this accuracy.…”
Section: Discussionmentioning
confidence: 99%